1985
DOI: 10.1128/aem.49.1.33-36.1985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selective media for assay of coliphages in sewage effluent and lake water

Abstract: Selective media, including EC medium, gram-negative broth, nutrient broth (with 0.05% sodium deoxycholate), and lactose broth (with 0.05% sodium deoxycholate), as well as nonselective nutrient and lactose broths, were compared for the enumeration of coliphages by the agar layer method from activated-sludge effluent and eutrophic-lake water from a lake receiving treated sewage effluent. Samples were plated directly or after chloroform treatment with Escherichia coli B, E. coli C, or a mixed host of both E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The use of direct pour plate assay methods for phage enumerations generally requires a number of steps to reduce or suppress the growth of naturally occurring micro-organisms. Incorporation of antibiotics or decontamination with chloroform (Osawa et al 1981a;Tartera and Jofre 1987), membrane filtration (Tartera and Jofre 1987) and selective media (Kennedy et al 1985) have been used for this purpose. The combined use of membrane filtration with incorporation of the antibiotic, nalidixic acid, has been used most commonly to increase overall assay selectivity.…”
Section: F ¦ -Specific Bacteriophagesmentioning
confidence: 99%
“…The use of direct pour plate assay methods for phage enumerations generally requires a number of steps to reduce or suppress the growth of naturally occurring micro-organisms. Incorporation of antibiotics or decontamination with chloroform (Osawa et al 1981a;Tartera and Jofre 1987), membrane filtration (Tartera and Jofre 1987) and selective media (Kennedy et al 1985) have been used for this purpose. The combined use of membrane filtration with incorporation of the antibiotic, nalidixic acid, has been used most commonly to increase overall assay selectivity.…”
Section: F ¦ -Specific Bacteriophagesmentioning
confidence: 99%
“…The bacteriophages mentioned above have been detected in surface waters (Araujo et al . 1997; Simkova and Cervenka 1981; Kennedy et al . 1985; Kfir et al .…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate the contaminating background flora, chemical treatment with chloroform was used, which produces a low rate of decontamination of the sample and a lower recovery of Bacteroides phages, although Tartera and Jofre (15) indicated a high resistance of these phages to chloroform. However, other authors have reported a decrease of the phage recovery after treatment of the samples with this chemical (8).…”
Section: Resultsmentioning
confidence: 66%